2012
DOI: 10.1016/j.marpolbul.2011.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ammonium concentrations from wastewater discharge depress primary productivity in the Sacramento River and the Northern San Francisco Estuary

Abstract: a b s t r a c tPrimary production in the Northern San Francisco Estuary (SFE) has been declining despite heavy loading of anthropogenic nutrients. The inorganic nitrogen (N) loading comes primarily from municipal wastewater treatment plant (WTP) discharge as ammonium (NH 4 ). This study investigated the consequences for river and estuarine phytoplankton of the daily discharge of 15 metric tons NH 4 -N into the Sacramento River that feeds the SFE. Consistent patterns of nutrients and phytoplankton responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 57 publications
(71 reference statements)
13
75
1
Order By: Relevance
“…Yoshiyama and Sharp (2006) examined a 26-yr dataset form the Delaware estuary and observed a "striking decline in production at NH 4 levels above a low threshold (10 mmol L À1 ) suggesting a strongly negative influence of NH 4 itself, or something that accompanies high NH 4 concentrations, or both". Depression of primary production and phytoplankton NH 4 uptake was recently reported for the Sacramento River, immediately downstream of the Sacramento Regional Wastewater Treatment Plant (SRWTP) (Parker et al, 2012). Suisun Bay chronically experiences high ambient NH 4 concentrations with 90% of NH 4 in Suisun Bay originating at the SRWTP (Jassby, 2008).…”
Section: Ammonium Effects On Phytoplankton Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…Yoshiyama and Sharp (2006) examined a 26-yr dataset form the Delaware estuary and observed a "striking decline in production at NH 4 levels above a low threshold (10 mmol L À1 ) suggesting a strongly negative influence of NH 4 itself, or something that accompanies high NH 4 concentrations, or both". Depression of primary production and phytoplankton NH 4 uptake was recently reported for the Sacramento River, immediately downstream of the Sacramento Regional Wastewater Treatment Plant (SRWTP) (Parker et al, 2012). Suisun Bay chronically experiences high ambient NH 4 concentrations with 90% of NH 4 in Suisun Bay originating at the SRWTP (Jassby, 2008).…”
Section: Ammonium Effects On Phytoplankton Productionmentioning
confidence: 95%
“…10 mmol N L À1 ) conditions and relatively low rNH 4 (ca. 0.10 mmol N L À1 h À1 ) characteristic of the northern SFE Dugdale et al, 2007;Parker et al, 2012) all minimize the potential impact of NH 4 regeneration on isotope dilution. Assuming an initial 15 N isotopic enrichment of 10% and NH 4 regeneration equivalent to uptake (0.1 mmol N L À1 h À1 ) the isotope enrichment would be reduced to 9.80% after 4-h resulting in an understate of NH 4 uptake by 2% (Dugdale and Wilkerson, 1986).…”
Section: Carbon and Nitrogen Assimilationmentioning
confidence: 99%
“…which can grow at a concentration of 3000 µmol NH 4 + l −1 in culture without experiencing growth inhibition (Pahl et al 2012). Most importantly, these thresholds are far above the concentrations of NH 4 + occurring in Suisun Bay that have been suggested to place diatoms at a disadvantage relative to dinoflagellates and cyanobacteria (Glibert 2010, Glibert et al 2011, and to reduce their growth (Dugdale et al 2007, Parker et al 2012, suggesting that the changes in phytoplankton composition and growth observed in those investigations were due to factors other than NH 4 + concentration. The present data also demonstrate that at nonlimiting concentrations, nutrient ratios are not good predictors of phytoplankton community composition.…”
Section: R H O D O M O N a S S Pmentioning
confidence: 78%
“…The genus Cyclotella has also been reported to dominate algal blooms in high-nutrient freshwater systems (Muylaert & Sabbe 1996, Wehr & Descy 1998, Mitrovic et al 2008, Beaver et al 2013. While these species have been reported to grow uninhibited in eutrophic estuaries at NH 4 + and NO 3 − concentrations approaching several hundred µmol l −1 (Collos et al 2005, Collos & Harrison 2014, other investigators have questioned whether concentrations of NH 4 + as low as 30 µmol l −1 near wastewater discharges negatively impact phytoplankton production (Thomas et al 1974, MacIsaac et al 1979, Glibert et al 2011, Parker et al 2012. Whereas 30 µmol NH 4 + l −1 is high for a marine system, culture investigations demonstrate that negative impacts on phytoplankton growth and production by nutrients typically occur at much greater concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation